The study of politics - Duverger, Maurice (Crowell, 1972)
This major contribution to political science by one of Europe's foremost theorists centres around the intellectual and political struggle between Marxism and liberral democracy - a struggle that has shaped Western experience for over a century and provides an historical perspective on contemporary society.